PARENTING DAN PENDIDIKAN SEKSUALITAS ANAK USIA DINI DI ALUMNA ISLAMIC SCHOOL - Rizki Natia Wiji; Silvia Anita Yuningsih; Fatma Nadia (Institut Kesehatan dan Teknologi Al Insyirah, 2020)
Early childhood sex education is important in child development. Given that all this time education in this phase is often ignored or poorly understood by the community. The aim of this study is to increase the knowledge of parents so that the parenting process about sex education in early childhood can be carried out. This type of quantitative research uses a quasi experimental research design with 2 groups of pre test and post test. The research was conducted at Alumna Islamic School in September 2019-March 2020. The research sample was 20 respondents with 10 control groups and 10 experimental groups. The sampling technique used purposive sampling. The research instrument used a questionnaire. Data processed by computerization. Data analysis used univariate and bivariate using Chi-Square statistical test. The results obtained were univariate age distribution of control group respondents aged 20-35 years (80%), DIII and S1 education (40%), civil servant occupations (40%), occasional sexuality education (50%), while the experimental group aged 20 -35 years (80%), S1 education (50%), private employees (30%) and frequent parenting (70%). The statistical test results obtained p value <0.05, which means that there is a difference in the average value of parenting and sexuality education of respondents pre and post intervention in the experimental group which is significantly different compared to the control group. It is recommended that parents increase their knowledge of early childhood education.